Sustainable development assessment of household e-waste reverse supply chains from an environmental ethic perspective - Xueying Yu; Zhiyuan Sun; Dongshi Sun; Rui He (Humanities & Social Sciences Communications)
Abstract The rapid increase in global e-waste generation, coupled with the shortening life cycles of electronic products, has intensified the environmental challenges associated with household e-waste. This study adopts an environmental ethics perspective to develop a comprehensive sustainability assessment framework for the household e-waste reverse supply chains. By employing fuzzy DEMATEL and ANP methods, the research examines key influencing factors and their interrelationships. The findings reveal that household e-waste recycling policies play a pivotal role (total influence weight: 0.083), significantly impacting public awareness, corporate environmental ethical responsibility, and the efficiency of recycling mechanisms. Furthermore, the establishment of formal collection points for orphan products emerges as a critical measure to enhance recycling efficiency. Based on these insights, we propose a tiered subsidy mechanism to increase recycling participation, encourage enterprises to develop eco-friendly recycling technologies, promote government-industry collaboration in establishing standardized collection facilities, and strengthen public awareness of proper household e-waste disposal through diverse outreach initiatives. These measures aim to foster resource recovery, mitigate environmental impact, and support the advancement of the circular economy.